2017
DOI: 10.5114/ceji.2017.67320
|View full text |Cite
|
Sign up to set email alerts
|

Detection of autoantibodies against carbonic anhydrase I and II in the plasma of patients with gastric cancer

Abstract: Cancer is the second leading cause of death and gastric cancer is the fourth most common cancer type worldwide. Investigation of autoantibodies in cancer patients has been a popular research area in recent years. The aim of the current study was to investigate carbonic anhydrase I and II (CA I and II) autoantibodies in the plasma of subjects with gastric cancer based on the information and considerations of autoimmune relation of gastric cancer. Anti-CA I and II antibody levels were investigated by ELISA in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For example, the members of the carbonic anhydrase (CA) family like CA7, CA9, CA12, CA3, CA6, CA14, CA13, CA2, and CA1 were targeted by numerous compounds, which implied that CA isoenzymes probably served as the key targets of HDW. It has long been acknowledged that CAs are extensively expressed in the gastrointestinal tract and play crucial roles in multiple physiological and pathological processes, such as transport of carbon dioxide, pH regulation, ion transport, formation of stomach acidity, bone resorption, calcification, and tumorigenesis [ 59 , 60 ]. Consider CA9, CA2, and CA1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the members of the carbonic anhydrase (CA) family like CA7, CA9, CA12, CA3, CA6, CA14, CA13, CA2, and CA1 were targeted by numerous compounds, which implied that CA isoenzymes probably served as the key targets of HDW. It has long been acknowledged that CAs are extensively expressed in the gastrointestinal tract and play crucial roles in multiple physiological and pathological processes, such as transport of carbon dioxide, pH regulation, ion transport, formation of stomach acidity, bone resorption, calcification, and tumorigenesis [ 59 , 60 ]. Consider CA9, CA2, and CA1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in 2007, it was presented that also in rheumatoid arthritis there are present aCAAs in serum, showing affinity to bind to carbonic anhydrase III in synovial membranes [ 16 ]. Up to date aCAAs have been described in patients with rheumatoid disorders (rheumatoid arthritis, Behçet's disease, lupus erythematosus, polymyositis, systemic sclerosis, and Sjögren syndrome) [ 16 18 ], digestive tract disorders (idiopathic chronic pancreatitis, primary biliary cirrhosis, autoimmune cholangitis, and gastric cancer) [ 18 , 19 ], endometriosis [ 18 ], Grave's disease [ 20 ], acute myeloid leukaemia [ 21 ], renal tubular acidosis [ 22 ] (significant influence on pathogenesis proved in the animal model of Sjögren's syndrome [ 23 ]), and end-stage kidney disease [ 24 ]. Moreover, autoantibodies against carbonic anhydrase II were proved to play an important role in pathogenesis of retinopathy [ 25 ] and these against CAVI seem to induce dry eye syndrome in Sjögren's syndrome [ 26 , 27 ].…”
Section: Carbonic Anhydrasesmentioning
confidence: 99%
“…Carbonic anhydrase 2 (CA2) encodes one of isozymes of carbonic anhydrase which catalyzes reversible hydration of carbon dioxide and plays a pivotal role in tissue pH homeostasis [20]. The expression of CA2 remains controversial in different cancers, it was reported to be upregulated in urinary bladder cancers [21], and CA2 autoantibody titers in gastric cancer patients were found higher compared to healthy subjects [22], while in esophageal adenocarcinoma, its expression was downregulated [23]. A previous study [24] conducted integrated bioinformatics analysis has found that lower expression of CA2 had a shorter overall survival compared to those with higher expression in COAD patients, its RNA and protein expression level were also validated in TCGA and the Human Protein Atlas, but without any experimental validation.…”
Section: Discussionmentioning
confidence: 99%